Distribution Pattern of the Benthic Meiofaunal Community Along the Depth Gradient of the Western Indian Continental Margin, Including the OMZ and Abyssal Plain - Sautya, Sabyasachi; Gaikwad, Santosh; Khokher, Sanofar; Pradhan, Umesh Kumar; Chatterjee, Soumya; Choudhury, Amita; Sahu, Balaram; Attri, Suman (Frontiers in Marine Science, 2021)
diversity; Continental margin; oxygen minimum zone; Arabian Sea; Indian Ocean Abstract The continental margin harbours variety of habitats that support incredible biodiversity and their ecosystem functioning in the oceans. The meiofauna is considered a significant component of the benthic faunal community from polar to tropical regions. The meiofaunal community in the deep Indian Ocean, especially along the depth gradient, is poorly investigated. The present study is aimed to explore the benthic meiofaunal community structure along the depth gradients and its associated environment in the western Indian continental margin (WICM) and abyssal plain in the eastern Arabian Sea. Sediment samples were collected from seven different depths (111 – 3918 m) along the WICM including the oxygen minimum zone (OMZ) and abyssal plain. A total of 22 taxa (groups) were encountered along the WICM. The nematodes (85%) were the most dominant taxa in all the depths, followed by copepods (11%), nauplii (5%) and polychaetes (1.36%). Our results suggest that a) the organic matter has accumulated in OMZ sites; b) a high amount of total organic carbon did not influence the meiofaunal density or biomass; c) oxygen and depth gradients were significant drivers of the meiofaunal community, low levels of oxygen contributed to lower taxa diversity and density at 485 m and 724 m depths; d) a significant relationship of meiofaunal density and biomass with chloroplastic pigment equivalent (CPE) values indicates pelagic-benthic coupling. Copepods, nauplii, tanaidaceans, isopods, kinorhynchs, cumaceans were affected by the low-oxygen conditions at the OMZ sites. Enhanced meiofaunal diversity, density and biomass at deeper sites (non-OMZ-D) was attributed to increased abundance of copepods, nauplii, tanaidaceans, isopods, kinorhynchs and cumaceans and were mostly concentrated on the surface sediment (0-4 cm) triggered by enhanced bottom-water oxygen and freshness of available food outside the OMZ except 3918 m. Therefore, the present study showed the meiofaunal community pattern with respect to depth gradients and their related environmental changes including OMZ along the WICM and abyssal plain in the Arabian Sea. Based on this study, the future extent of these underestimated marine ecosystems must be considered a priority to understand its functional consequences.